Answer:
We have 6( n - 24 ) = 8N;
Then 6n - 144 = 8N;
-144 = 8N - 6N;
-144 = 2N;
N = (-144)÷2;
N = - 72;
Step-by-step explanation:
Answer:
36
Step-by-step explanation:
24^2 = (12)(12+x)
576 = 144 + 12x
432 = 12x
36 = x
Answer:
Step-by-step explanation:
x² - 2x + y² - 4y - 4 = 0
x² - 2x + y² - 4y = 4
complete the squares
(x² - 2x + x₀) + (y² - 4y + y₀) = 4
the unknown number will be the square of half of the x¹ coefficient
(x² - 2x + 1) + (y² - 4y + 4) = 4 + 1 + 4
(x - 1)² + (y - 2)² = 9
This tells us that the circle is centered on (1, 2)
Which is also a point on the diameter
2x - y + a = 0
a = y - 2x
a = 2 - 2(1)
a = 0
Answer:
Solve for y in the second equation
Step-by-step explanation:
We assume your system is ...
Dividing <em>the </em><em>second equation</em> by 3 gives ...
-3x +y = 1
so an expression for y without fractions can be found by <em>solving for y</em>, that is, by adding 3x:
y = 3x +1
_____
<em>Comment on alternate solution</em>
We'd be tempted to solve the first equation for -9x and substitute for that.
-9x = 10 -4y
(10 -4y) +3y = 3 . . . . . substitute for -9x
-y = -7 . . . . . . . . . . . . . simplify, subtract 10
y = 7 . . . . . . . . . . . . . . multiply by -1
Answer:
B
Step-by-step explanation:
hope it helps you
please follow me